Epoxy resin composition, structure-energy storage integrated solid supercapacitor and preparation method of structure-energy storage integrated solid supercapacitor
By using epoxy resin composition and polyaniline/carbon fiber/rGO composite materials, a structure-energy storage integrated solid supercapacitor was prepared, which solved the problem that existing carbon fiber composite materials could not have both material structure and energy storage, and achieved efficient electrochemical and mechanical performance improvements.
Patent Information
- Application Number
- CN202411699070.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-07
AI Technical Summary
Existing carbon fiber composite materials are difficult to have both material structure and energy storage performance, and cannot achieve a balance between material structure and energy storage.
An epoxy resin composition is used as the structural electrolyte and a polyaniline/carbon fiber/rGO composite material is combined as the electrode material to prepare a structure-energy storage integrated solid supercapacitor through chemical interface method and in-situ self-assembly method.
The specific capacitance and mechanical properties of solid-state supercapacitors are significantly improved, the area capacitance is increased by two orders of magnitude, the shear strength is also improved by nearly 40%, and high-efficiency electrochemical performance is maintained after cyclic charging and discharging.
Smart Images

Figure BDA0005152808270000011 
Figure BDA0005152808270000031 
Figure BDA0005152808270000061
Abstract
Description
Technical Field
[0001] The present invention relates to the field of composite materials and electrochemical technology, and in particular to an epoxy resin composition and a structure-energy storage integrated solid-state supercapacitor and a preparation method thereof. Background Art
[0002] With the increasing application of multifunctional structural materials in the field of energy storage, carbon fiber composites have gradually become one of the preferred structural materials for energy storage devices due to their excellent mechanical properties and electrical conductivity. However, how to achieve a balance between material structure and energy storage, especially optimizing the comprehensive performance of electrode materials and electrolytes, remains the current research focus.
[0003] Therefore, how to obtain a structure-energy storage integrated solid-state supercapacitor and its preparation method is a technical problem that needs to be solved at present. Summary of the invention
[0004] The object of the present invention is to provide an epoxy resin composition and a structure-energy storage integrated solid-state supercapacitor and a preparation method thereof, so as to solve the technical problem that existing carbon fiber composite materials cannot have both material structure and energy storage performance.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides an epoxy resin composition, which is composed of the following components in parts by weight:
[0007]
[0008] Furthermore, the conductive ionic liquid comprises one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1,3-dimethylimidazolium bis(fluoromethanesulfonyl)imide salt, 1,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide salt, N,N-dimethylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, N,N-dimethylpyrrolidine tetrafluoroborate and N-methyl-N-ethylpyrrolidine bis(fluoromethanesulfonyl)imide salt.
[0009] Further, the silicon-containing epoxy resin comprises one or more of glycidylamine epoxy silicone resin, polyisocyanurate-oxazolidone resin and silicone-modified epoxy resin;
[0010] The biphenyl epoxy resin includes one or more of EPON1001F, EPON1007F, EPON828, EPON862 and EPON828ELW.
[0011] Furthermore, the curing agent comprises one or more of 4-methylcyclohexane dianhydride, isopropanolamine, triethylenetetramine and polyetheramine.
[0012] Furthermore, the composite mass ratio of the tertiary amine and the substituted urea is 1 to 5:1, the tertiary amine comprises one or more of triethylamine, triethanolamine, benzyldimethylamine, bicyclic amidine, o-hydroxybenzyldimethylamine and pyridine; the substituted urea comprises N-p-chlorophenyl-N,N'-dimethylurea and / or N-(3,4-dichlorophenyl)-N,N'-dimethylurea.
[0013] The present invention also provides a structure-energy storage integrated solid-state supercapacitor, which uses a polyaniline / carbon fiber / rGO composite material as an electrode material and an epoxy resin composition as a structural electrolyte to assemble into a solid-state supercapacitor;
[0014] The polyaniline / carbon fiber / rGO composite material is composited with polyaniline, graphene oxide and carbon fiber.
[0015] The present invention also provides a method for preparing a structure-energy storage integrated solid-state supercapacitor, comprising the following steps:
[0016] (1) activating the carbon fiber cloth and immersing it in a dichloromethane solution of aniline, taking it out, washing it, and drying it to obtain a polyaniline / carbon fiber composite material;
[0017] (2) placing the polyaniline / carbon fiber composite material into a graphene oxide solution for in-situ self-assembly, and then reducing the product to obtain a polyaniline / carbon fiber / rGO composite material;
[0018] (3) A solid-state supercapacitor was assembled using an epoxy resin composition as the structural electrolyte and a polyaniline / carbon fiber / rGO composite material as the electrode material.
[0019] Furthermore, the concentration of the dichloromethane solution of aniline is 0.1-0.3 mol / L, and the drying temperature is 20-70°C.
[0020] Furthermore, the in-situ self-assembly time is 2 to 4 hours, the reduction is performed using HI steam, the reduction temperature is 90 to 100° C., and the reduction time is 1 to 3 hours.
[0021] Beneficial effects of the present invention:
[0022] The present invention adopts a chemical interface method to prepare a polyaniline / carbon fiber composite material at different temperatures. Experiments show that as the reaction temperature increases, the morphology of the carbon fiber surface becomes more three-dimensional and the pore structure is more obvious.
[0023] The present invention adopts an in-situ self-assembly method to self-assemble graphene oxide onto the surface of the composite material, and the specific capacitance of the finally obtained polyaniline / carbon fiber / rGO composite material is significantly improved, up to 953.4F / g, and the capacitance retention rate is 92.28% after the composite material is cyclically charged and discharged for 1000 times.
[0024] The epoxy resin composition of the present invention utilizes different types of epoxy resins to complement each other in performance, and by adding a conductive ionic liquid, the electrochemical performance of the epoxy resin is enhanced by utilizing the characteristics of the ionic liquid. The epoxy resin can be used in an electrolyte material to improve the electrochemical performance of a battery.
[0025] The epoxy resin composition of the present invention has strong interfacial compatibility with electrode materials and is used as a structural electrolyte in supercapacitors to assemble solid-state supercapacitors. The capacitance and shear test results show that the supercapacitor exhibits good reversibility, significantly improves its area capacitance, and enhances its mechanical properties. DETAILED DESCRIPTION
[0026] The present invention provides an epoxy resin composition, which is composed of the following components in parts by weight:
[0027]
[0028] In the present invention, the content of diglycidyl phthalate is preferably 35 to 45 parts by mass, more preferably 38 to 42 parts, and even more preferably 40 parts.
[0029] In the present invention, the content of the polyethylene glycol diglycidyl ether is preferably 8 to 16 parts by mass, more preferably 10 to 15 parts, and even more preferably 12 to 13 parts.
[0030] In the present invention, the content of the silicon-containing epoxy resin is preferably 12 to 25 parts by mass, and more preferably 15 to 20 parts by mass.
[0031] In the present invention, the content of the biphenyl epoxy resin is preferably 12 to 25 parts by mass, and more preferably 15 to 20 parts by mass.
[0032] In the present invention, the content of the conductive ionic liquid is preferably 6 to 8 parts by mass, and more preferably 7 parts by mass.
[0033] In the present invention, the content of the curing agent is preferably 6 to 8 parts by mass, and more preferably 7 parts by mass.
[0034] In the present invention, the content of the accelerator compounded of the tertiary amine and the substituted urea is preferably 2 to 4 parts by mass, and more preferably 3 parts.
[0035] In the present invention, the conductive ionic liquid comprises one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1,3-dimethylimidazolium bis(fluorosulfonyl)imide salt, 1,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide salt, N,N-dimethylpyrrolidine bis(trifluoromethylsulfonyl)imide salt, N,N-dimethylpyrrolidine tetrafluoroborate and N-methyl-N-ethylpyrrolidine bis(fluorosulfonyl)imide salt, preferably one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide salt, 1,3-dimethylimidazolium bis(fluorosulfonyl)imide salt and 1,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide salt.
[0036] In the present invention, the silicon-containing epoxy resin comprises one or more of glycidylamine epoxy silicone resin, polyisocyanurate-oxazolidone resin and silicone-modified epoxy resin, preferably silicone resin, more preferably one or more of methylphenyl silicone resin, fluorosilicone resin, vinyl silicone resin and amino silicone resin.
[0037] In the present invention, the biphenyl epoxy resin comprises one or more of EPON1001F, EPON1007F, EPON828, EPON862 and EPON828ELW, preferably EPON862 and / or EPON828ELW.
[0038] In the present invention, the curing agent comprises one or more of 4-methylcyclohexane dianhydride, isopropanolamine, triethylenetetramine and polyetheramine, preferably 4-methylcyclohexane dianhydride and / or isopropanolamine.
[0039] In the present invention, the composite mass ratio of the tertiary amine and the substituted urea is 1 to 5:1, preferably 2 to 4:1, and more preferably 3:1; the tertiary amine comprises one or more of triethylamine, triethanolamine, benzyldimethylamine, bicyclic amidine, o-hydroxybenzyldimethylamine and pyridine, preferably one or more of triethylamine, triethanolamine and pyridine; the substituted urea comprises N-p-chlorophenyl-N,N'-dimethylurea and / or N-(3,4-dichlorophenyl)-N,N'-dimethylurea, preferably N-p-chlorophenyl-N,N'-dimethylurea.
[0040] The present invention also provides a structure-energy storage integrated solid-state supercapacitor, which uses a polyaniline / carbon fiber / rGO composite material as an electrode material and an epoxy resin composition as a structural electrolyte to assemble into a solid-state supercapacitor;
[0041] The polyaniline / carbon fiber / rGO composite material is composited with polyaniline, graphene oxide and carbon fiber.
[0042] The present invention also provides a method for preparing a structure-energy storage integrated solid-state supercapacitor, comprising the following steps:
[0043] (1) activating the carbon fiber cloth and immersing it in a dichloromethane solution of aniline, taking it out, washing it, and drying it to obtain a polyaniline / carbon fiber composite material;
[0044] (2) placing the polyaniline / carbon fiber composite material into a graphene oxide solution for in-situ self-assembly, and then reducing the product to obtain a polyaniline / carbon fiber / rGO composite material;
[0045] (3) A solid-state supercapacitor was assembled using an epoxy resin composition as the structural electrolyte and a polyaniline / carbon fiber / rGO composite material as the electrode material.
[0046] In the present invention, the concentration of the dichloromethane solution of aniline is 0.1-0.3 mol / L, preferably 0.1-0.2 mol / L, and more preferably 0.1 mol / L; the drying temperature is 20-70°C, preferably 30-60°C, and more preferably 40-50°C.
[0047] In the present invention, the in-situ self-assembly time is 2 to 4 hours, preferably 3 hours; the reduction is performed using HI steam, the reduction temperature is 90 to 100° C., preferably 95° C.; the reduction time is 1 to 3 hours, preferably 2 hours.
[0048] In the present invention, the specific steps of assembling into a solid-state supercapacitor are:
[0049] An electrolyte solution is prepared by mixing a lithium salt, a plasticizer and an epoxy resin composition; two aluminum bars are attached to both sides of a polyaniline / carbon fiber / rGO composite material to make an activated carbon fiber electrode sheet; the activated carbon fiber electrode sheet and a glass fiber separator are immersed in the electrolyte solution together; then, the activated carbon fiber electrode sheet is placed on the front and back sides of the glass fiber membrane to assemble a symmetrical layered supercapacitor; the layered supercapacitor is moved into a vacuum bag, vacuum-sealed, and then transferred to an oven for curing at 80°C for 8 hours to obtain a solid-state supercapacitor.
[0050] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0051] Example 1
[0052] 1. Preparation of epoxy resin composition: Mix the following components in parts by weight:
[0053]
[0054] The mass ratio of triethylamine to N-p-chlorophenyl-N,N'-dimethylurea is 3:1.
[0055] 2. Preparation of structure-energy storage integrated solid-state supercapacitor:
[0056] (1) The carbon fiber was placed in a 1M KOH solution for 3 h, taken out and dried, and then kept at 800°C in a tube furnace for 30 min. After washing with deionized water, it was dried at 80°C to obtain a preactivated carbon fiber cloth. Then, it was immersed in a 0.1 mol / L aniline dichloromethane solution, taken out and washed, and dried at 20°C, 50°C and 70°C to obtain a polyaniline / carbon fiber composite material, which was recorded as P-20, P-50 and P-70 respectively.
[0057] (2) placing the polyaniline / carbon fiber composite material into a graphene oxide solution for in-situ self-assembly, and then reducing the product in an atmosphere of HI vapor at a temperature of 95° C. to obtain a polyaniline / carbon fiber / rGO composite material;
[0058] (3) Using the epoxy resin composition as the structural electrolyte and the polyaniline / carbon fiber / rGO composite material as the electrode material, a solid supercapacitor is assembled, and the specific steps are as follows:
[0059] An electrolyte solution is prepared by mixing a lithium salt, a plasticizer and an epoxy resin composition; two aluminum bars are attached to both sides of a polyaniline / carbon fiber / rGO composite material to make an activated carbon fiber electrode sheet; the activated carbon fiber electrode sheet and a glass fiber separator are immersed in the electrolyte solution together; then, the activated carbon fiber electrode sheet is placed on the front and back sides of the glass fiber membrane to assemble a symmetrical layered supercapacitor; the layered supercapacitor is moved into a vacuum bag, vacuum-sealed, and then transferred to an oven for curing at 80°C for 8 hours to obtain a solid-state supercapacitor.
[0060] The electrochemical performances of the obtained P-20, P-50 and P-70 materials are compared, as shown in Table 1.
[0061] Table 1 Comparison of electrochemical performance
[0062]
[0063]
[0064] It can be seen that as the temperature increases, the pore structure of the carbon fiber surface gradually becomes obvious, which helps to improve the specific capacitance and conductivity. The P-70 sample exhibits the best electrochemical performance, with a specific capacitance of 819.2F / g, the lowest impedance, and the smallest diffusion resistance.
[0065] The properties of P-70 and polyaniline / carbon fiber / rGO composites are compared as shown in Table 2.
[0066] Table 2 Performance comparison of P-70 and polyaniline / carbon fiber / rGO composites
[0067]
[0068] Example 2
[0069] Same as Example 1, except that the epoxy resin composition is prepared as follows:
[0070]
[0071] Wherein, the mass ratio of triethanolamine to N-p-chlorophenyl-N,N'-dimethylurea is 4:1.
[0072] The preparation of the structure-energy storage integrated solid-state supercapacitor is the same as in Example 1.
[0073] Example 3
[0074] Same as Example 1, except that the epoxy resin composition is prepared as follows:
[0075]
[0076] The mass ratio of pyridine to N-(3,4-dichlorophenyl)-N,N'-dimethylurea is 1:1.
[0077] Example 4
[0078] Same as Example 1, except that the epoxy resin composition is prepared as follows:
[0079]
[0080] The mass ratio of triethylamine to N-(3,4-dichlorophenyl)-N,N'-dimethylurea is 4:1.
[0081] Example 5
[0082] Same as Example 1, except that the epoxy resin composition is prepared as follows:
[0083]
[0084] The mass ratio of benzyldimethylamine to N-p-chlorophenyl-N,N'-dimethylurea is 1:1.
[0085] The epoxy resin compositions obtained in Examples 1 to 3 were used as electrolytes, and the conductivity and mechanical properties of the electrolytes were tested. The results are shown in Table 3 below.
[0086] Table 3 Electrolyte property test
[0087] project Ionic conductivity (mS.cm-1) Tensile strength(MPa) Compression strength(MPa) Example 1 0.98 35 16 Example 2 1.23 26 15 Example 3 1.68 20 13
[0088] It can be seen from the above experimental results that with the increase of the content of polyethylene glycol diglycidyl ether in the epoxy resin, the ionic conductivity of the electrolyte can reach a maximum of 1.68mS.cm-1, but at the same time, both the tensile strength and the compressive strength decrease. When the content reaches 15wt%, the tensile strength decreases significantly; therefore, when the content is 10wt%, the ionic conductivity, tensile strength and compressive strength reach the optimal balance point, which is suitable for use in supercapacitors.
[0089] The performance of the solid supercapacitors obtained in Examples 1 to 5 was subjected to capacitance (scan rate: 10 mV / s) and shear tests. The results are shown in Table 4 below.
[0090] Table 4 Performance test of solid-state supercapacitor
[0091] project Area capacitance (mF / cm2) Shear strength(MPa) Example 1 29.8 18.41 Example 2 30.8 19.53 Example 3 27.2 17.24 Example 4 29.2 18.62 Example 5 30.1 18.41
[0092] The present invention also conducted the above experimental tests on capacitors assembled from carbon fiber cloth that has not been treated with the epoxy resin composition, and the results are: the area capacitance is only 0.31mF / cm2, and the shear strength is only 12.63MPa. From the above results, it can be seen that the epoxy resin composition and the polyaniline / carbon fiber / rGO composite material have strong interface compatibility, and the solid-state supercapacitor prepared by combining the two effectively improves the area capacitance and shear strength of the capacitor. The area capacitance is increased by two orders of magnitude compared to the capacitor prepared without adding the epoxy resin composition, and the shear strength is also increased by nearly 40%.
[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An epoxy resin composition, characterized in that It is composed of the following components in parts by mass:
2. The epoxy resin composition according to claim 1, characterized in that The conductive ionic liquid comprises one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1,3-dimethylimidazolium bis(fluoromethanesulfonyl)imide salt, 1,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide salt, N,N-dimethylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, N,N-dimethylpyrrolidine tetrafluoroborate and N-methyl-N-ethylpyrrolidine bis(fluoromethanesulfonyl)imide salt.
3. The epoxy resin composition according to claim 1 or 2, characterized in that The silicon-containing epoxy resin comprises one or more of glycidylamine epoxy silicone resin, polyisocyanurate-oxazolidone resin and silicone-modified epoxy resin; The biphenyl epoxy resin includes one or more of EPON1001F, EPON1007F, EPON828, EPON862 and EPON828ELW.
4. The epoxy resin composition according to claim 3, characterized in that The curing agent comprises one or more of 4-methylcyclohexane dianhydride, isopropanolamine, triethylenetetramine and polyetheramine.
5. The epoxy resin composition according to claim 1, 2 or 4, characterized in that: The composite mass ratio of the tertiary amine and the substituted urea is 1 to 5:1, the tertiary amine comprises one or more of triethylamine, triethanolamine, benzyldimethylamine, bicyclic amidine, o-hydroxybenzyldimethylamine and pyridine; the substituted urea comprises N-p-chlorophenyl-N,N'-dimethylurea and / or N-(3,4-dichlorophenyl)-N,N'-dimethylurea.
6. A structure-energy storage integrated solid-state supercapacitor, characterized in that: A solid supercapacitor is assembled using a polyaniline / carbon fiber / rGO composite material as an electrode material and the epoxy resin composition according to any one of claims 1 to 5 as a structural electrolyte; The polyaniline / carbon fiber / rGO composite material is composited with polyaniline, graphene oxide and carbon fiber.
7. The method for preparing a structure-energy storage integrated solid-state supercapacitor according to claim 6, characterized in that: The following steps are involved: (1) activating the carbon fiber cloth and immersing it in a dichloromethane solution of aniline, taking it out, washing it, and drying it to obtain a polyaniline / carbon fiber composite material; (2) placing the polyaniline / carbon fiber composite material into a graphene oxide solution for in-situ self-assembly, and then reducing the product to obtain a polyaniline / carbon fiber / rGO composite material; (3) The epoxy resin composition according to any one of claims 1 to 5 is used as a structural electrolyte and the polyaniline / carbon fiber / rGO composite material is used as an electrode material to assemble a solid supercapacitor.
8. The method for preparing a structure-energy storage integrated solid-state supercapacitor according to claim 7, characterized in that: The concentration of the dichloromethane solution of aniline is 0.1-0.3 mol / L, and the drying temperature is 20-70°C.
9. The method for preparing a structure-energy storage integrated solid-state supercapacitor according to claim 7 or 8, characterized in that: The in-situ self-assembly time is 2 to 4 hours, the reduction is performed using HI steam, the reduction temperature is 90 to 100° C., and the reduction time is 1 to 3 hours.